Principles of pavement engineering - Thom, Nick (Emerald Publishing Limited, 2024)
Principles of Pavement Engineering, Third edition is an essential reference on fundamental principles of pavement engineering, showing how to design, construct, evaluate and maintain pavements of all types. Over 27 chapters the book provides systematic coverage of the subject and in-depth analysis of principles underlying material behaviour, pavement design, and maintenance. This third edition has been comprehensively updated to cover recent industry developments including increased emphasis on sustainability, decarbonisation and climate change; as well as warm and cold-mix asphalts, non-standard bitumen additives, designing with stress-absorbing membrane interlayers, whole-life costing and improved methods for drainage design. The book features a complete reference on fundamental principles of pavement engineering; accessibly written, with ample use of explanatory diagrams, photographs, and chapter summaries to support understanding; worked examples throughout the text illustrate applications to practical problems; additional resources include access to an extensive collection of design calculation spreadsheets. Principles of Pavement Engineering, Third edition offers broad and applicable coverage of the subject making it a key reference for practising pavement engineers at all levels, as well as students and graduates.